Documentário de percurso esportivo: processos de criação da jornada - Abe, Luciano Koji (2022)
This thesis approaches the documentary on trajectory in the sport, a type of work in which the whole process is followed and recorded, from the behind-the-scenes preparation of athletes, up to the conclusion of a project, a championship or an event, from the very beginning to the very end, as well as its outcome, being it a victory or defeat. I seek to discuss and analyze how documentaries on trajectories in the sport portrait athletes from different areas according to the theory of the journey of the archetypal hero, developed by Joseph Campbell, researcher on the fields of mythology, psychology, and comparative religion, in his book The Hero with a Thousand Faces, later adapted to fiction movies by the screenwriter Christopher Vogler in the work The Writer’s Journey. According to the theory regarding the myth of the archetypal hero, there is a cycle in which the protagonist goes from the common world to the world of adventure, facing challenges and overcoming obstacles before returning home enriched by invaluable experience. The following work focuses on the sport theme due to the fact that athletes and classic heroes are very much alike. In fact, some of them are deemed as gods due to their invincibility. The thesis set roots in the theories of Cecilia Almeida Salles, with the importance of the theories of creation as net, and the material used for analysis is constituted by the documentaries Free Solo, Murderball – Passion and Glory and Brothers in the Boxing Ring